Acute effect of Capparis spinosa root extracts on rat articular pain. (4th December 2016) - Maresca, Mario; Micheli, Laura; Di Cesare Mannelli, Lorenzo; Tenci, Barbara; Innocenti, Marzia; Khatib, Mohamad; Mulinacci, Nadia; Ghelardini, Carla
Abstract: Ethnopharmacological relevance: Capparis spinosa L. originates from dry regions of Asia and Mediterranean basin. In traditional medicine of these areas, infusions from caper root are considered to be beneficial for the treatment of rheumatism, gout and against abdominal pains. Aim of the study: To evaluate the pain relieving properties of a Syrian cultivar of Capparis spinosa roots in rat models of osteoarthritis and rheumatoid arthritis. Materials and methods: Decoction (DEC) and hydroalcoholic extract (EtH2 O) were obtained from powdered roots; the latter was further separated in CH2 Cl2 and aqueous (H2 O-Res) fractions. The extracts were characterized in terms of spermidine alkaloids by HPLC/DAD/MS and stachydrine by NMR. Different amount of free and glycosilated forms of capparispine and analogues (from 0.5% w/w for DEC up to 7.6% w/w for CH2 Cl2 fraction) were detected. Rat models of rheumatoid arthritis and osteoarthritis were induced by the intra-articular administration of Complete Freund's Adjuvant (CFA) or monosodium iodoacetate (MIA), respectively. Results: Fourteenth days after CFA or MIA injection, the different preparations of Capparis spinosa (3, 30, 100 and 300 mg kg −1 ) were acutely administered p.o.. Powdered roots (300 mg kg −1 ), DEC (100 mg kg −1 ), and EtH2 O (300 mg kg −1 ) significantly reduced hypersensitivity to mechanical noxious stimuli as well as spontaneous pain evaluated as hind limb bearing alterations in both models. The CH2 Cl2 and the H2 O-Res (30 mg kg −1 ) were the most potent in reverting pain threshold alterations despite the different content of free alkaloids. Conclusions: Capparis spinosa extracts relieved pain related to rheumatoid arthritis and osteoarthritis after single administration. A synergistic effect due to a specific "phytochemical mixture" is suggested. Graphical abstract: